Post-traumatic cyst-like lesion in children: case report and the literature review. Issue 2 (March 2016) - Angelliaume, Audrey; Simon, Anne-Laure; Tanase, Anca; Mazda, Keyvan; Ilharreborde, Brice
Abstract : Reports of post-traumatic cyst-like lesions in children are rare. These lesions occur between 1.5 and 3 months after a fracture. They are more frequent after a distal radius greenstick fracture. Conventional radiographs show a metaphyseal radiolucent lesion inside the most recent subperiosteal bone, adjacent to the initial fracture line. Post-traumatic cyst-like lesions are benign, asymptomatic, nonexpansive, and regress spontaneously. Two typical cases are described in the following report with a literature review of the etiology and main features of these lesions. Level of evidence: Level V, case report.